Social media influencer’s influence on the travel decisions with respect to Kaveri delta region - T, Priyanga; J, Ashokkumar (Journal of Management and Science, 2023)
After the advent of social media applications, the consumers of tourism sector rely on the social media influencers information while planning trip to a particular destination. Many previous studies were focused on the effectiveness of social media interactions in spreading content about tourism destinations. The current was aimed to examine the role of social media influencers towards attracting the social media users to visit the Tourist spot with respect to the Kaveri delta region of Tamil Nadu. The study intended to examine the consumers Pre-Purchase, Purchase decision and post-Purchase decision while scheduling a trip based on the inspiration from the social media influencer. The research instrument was circulated using social media applications and 278 valid responses was collected using Purposive sampling method. The responses were analyzed using Microsoft Excel, SPSS and Amos. The Findings shows that the research instrument was reliable and valid. Further, the result of the Path analysis demonstrates that the social media users are influenced by the social media influencers while planning their trip to the Tourist spot at the Kaveri delta region of Tamil Nadu. The findings revealed that the social media users are not willing to post their post visit experiences from the Tourist spot which could influence the future travelers.